Unveiling Portugal’s Geothermal Landscape: Insights from the IGCP636 Annual Meeting 2023 - Gutiérrez-Soleibe, Fernando; Miranda, Mafalda M.; Goldoni De Souza, Mariana; Chapman, Fiona M.; Gold , Abra R.; Lee, Victoria M.; Gascuel, Violaine; Thomas, Garen J.; Thibault, Michaël; Raymond, Jasmin; Blessent, Daniela; Malo, Michel; et al. (Geologija, 2025)
Abstract is not available